Kyrgyz Republic : Insights on Household Access to Water Supply and Sanitation - World Bank Group (World Bank, Washington, DC, 2015)
This note has been prepared as part of the work program on multi-dimensional poverty in the Kyrgyz Republic to raise awareness of poverty dimensions, which in turn should help accelerate the development of water supply and sanitation services, and necessary reforms in the Kyrgyz Republic. The note analyzes the quality and reliability of the Integrated Households Survey (KIHS) data to measure access to water supply and sanitation services. The household survey was conducted by the National Statistics Committee (NSC) of the Kyrgyz Republic. It is representative at the national, rural/urban, and oblast levels. Using survey data we analyze the consumption of water supply and sanitation services at the household level with a focus on access, quality, and expenditures.